ENCYCLOPEDIA OF WORLD TRAVEL - Doubleday, Nelson (edición) (1961)
CONTENIDO: V. 1 UNITED STATES, CANADA, MEXICO, CENTRAL AMERICA, BERMUDA, THE BAHAMAS, THE CARIBBEAN, SOUTH AMERICA. -- V. 2 EUROPE, AFRICA, THE MIDDLE EAST, ASIA, THE PACIFIC